A method for preparing a flexible copper clad laminate

The polymer film is activated by a high-energy non-metallic ion beam and metal ions are injected on its surface to form an interpenetrating network structure. Combined with intermittent Ar+ bombardment, the problem of insufficient bonding strength between the copper film and the polymer substrate is solved, and the bonding strength and stability of the flexible copper clad plate is significantly improved.

CN115948712BActive Publication Date: 2025-03-25LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211645091.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-21
Publication Date
2025-03-25
Estimated Expiration
2042-12-21

AI Technical Summary

Technical Problem

In the prior art, when preparing flexible copper clad plate by sputtering plating, the bonding strength between the copper film and the polymer substrate is insufficient, resulting in the copper film being easily shedded during bending, torsion and stretching.

Method used

The polymer film surface is etched and activated by using a high-energy non-metallic ion beam to form an activated polymer film, and then metal ions are injected on its surface by magnetron sputtering to form a polymer-metal interpenetrating network structure interface, and then copper film is deposited at this interface, and intermittent Ar+ bombardment is used during the deposition process to improve the bonding strength between the copper film and the polymer substrate.

Benefits of technology

The peel strength between the surface copper film of flexible copper clad plate and the polymer substrate is significantly improved, the risk of brittle shedding of the copper film is reduced, and the curling phenomenon of the polymer film due to the high internal stress of the copper film is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115948712B_ABST
    Figure CN115948712B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of flexible copper-clad laminates, and in particular to a method for preparing a flexible copper-clad laminate. The present invention provides a method for preparing a flexible copper-clad laminate, comprising the following steps: using a high-energy non-metallic ion beam to etch and activate the surface of a polymer film to obtain an activated polymer film; using magnetron sputtering to inject metal ions onto the surface of the activated polymer film to obtain a polymer-metal interpenetrating network structure interface; depositing a copper film on the polymer-metal interpenetrating network structure interface, and while depositing the copper film, using intermittent Ar + The copper film is bombarded. The preparation method can significantly improve the peeling strength between the copper film on the surface of the flexible copper clad laminate and the polymer substrate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of flexible copper clad laminates, and in particular to a preparation method of a flexible copper clad laminate. Background Art

[0002] Flexible copper clad laminate (FCCL) refers to a copper clad laminate formed by bonding copper foil to one or both sides of a flexible insulating material such as polyester (PET) or polyimide (PI) film through a certain process. It is widely used in aerospace equipment, navigation equipment, aircraft instruments, guidance systems, and electronic products such as mobile phones, digital cameras, digital video cameras, automotive satellite positioning devices, LCD TVs, and laptops. With the rapid development of electronic technology, the dosage of FCCL has steadily increased, and the production scale has continued to expand, especially for high-performance FCCL with polyimide film as the substrate, which has a significant demand and growth trend.

[0003] The traditional preparation method of flexible copper clad laminate is to use adhesive to bond the flexible substrate film to the metal copper foil. In addition, there are lamination, coating and sputtering methods. The lamination method uses PI resin as the substrate, and coats thermoplastic PI resin on one or both sides of it. It is first hardened at high temperature and then re-melted at high temperature and high pressure to press the thermoplastic PI resin with copper foil to form a product. The production equipment is simple, the product has good adhesion and dimensional stability, and is suitable for the preparation of single-sided, double-sided and multi-sided FCCL, but the manufacturing process of the main component hot oil high-temperature pressing roller is relatively complicated. The coating method is to coat the PI prepolymer on the surface of the copper foil, and then obtain it after desolventization and high-temperature imidization. It is mainly used for the preparation of single-sided FCCL. The preparation process of this method is relatively simple and easy to implement, but it is difficult to achieve a high level of adhesion and dimensional stability of the product at the same time. Sputtering deposition is a more advanced method for preparing FCCL. In a vacuum environment, energetic particles are used to bombard the surface of the target material, so that the target atoms or ions are bombarded and detached, and grow into a thin film on the surface of the substrate. This method can avoid the use of adhesives, replace the electroplating process, and realize the one-step method of directly preparing FCCL on the surface of a flexible substrate. It has the advantages of precise control of deposition speed and the ability to prepare multilayer films. However, due to the poor adhesion of copper on polymer substrates such as PI, stress concentration will occur at the interface between the sputtered copper film and the substrate during bending, torsion and stretching, causing the surface copper film to fall off. Therefore, improving the bonding strength between the copper film and the polymer substrate is a key issue encountered in the development of sputtering plating methods. Summary of the invention

[0004] The object of the present invention is to provide a method for preparing a flexible copper clad laminate, which can significantly improve the peel strength between a copper film on the surface of the flexible copper clad laminate and a polymer substrate.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing a flexible copper clad laminate, comprising the following steps:

[0007] A high-energy non-metallic ion beam is used to etch and activate the surface of the polymer film to obtain an activated polymer film;

[0008] Using magnetron sputtering, metal ions are injected into the surface of the activated polymer film to obtain a polymer-metal interpenetrating network structure interface;

[0009] A copper film is deposited on the interface of the polymer-metal interpenetrating network structure, and while depositing the copper film, an intermittent Ar + The copper film is bombarded to obtain the flexible copper clad laminate.

[0010] Preferably, the polymer film is a polyimide film or a polyethylene terephthalate film.

[0011] Preferably, before performing the etching activation, the polymer film is further cleaned with a solvent;

[0012] The solvent used in the solvent cleaning is petroleum ether or alcohol;

[0013] The solvent cleaning is carried out under ultrasonic conditions, and the ultrasonic time is 5 to 15 minutes.

[0014] Preferably, the etching activation is performed under vacuum conditions;

[0015] The vacuum degree of the vacuum is <1×10 -4 Pa.

[0016] Preferably, the high energy non-metal ion beam is Ar + ,Ar + +H + or Ar + +N + ;

[0017] The Ar + Plasma generated by Ar, wherein the flow rate of Ar is 80 sccm;

[0018] The Ar + +H + Plasma generated by Ar+H2, wherein the flow rates of Ar and H2 are 80 sccm and 20 sccm respectively;

[0019] The Ar + +N + The plasma is generated by Ar+N2, and the flow rates of Ar and N2 are 80sccm and 20sccm respectively.

[0020] Preferably, the etching activation bias voltage is -200 to -250 V, and the time is 5 to 20 minutes.

[0021] Preferably, the metal element corresponding to the metal ion is Cr, Ni, Nb or Cu.

[0022] Preferably, the conditions of the magnetron sputtering are: Ar flow rate is 180 to 250 sccm, substrate bias voltage is -60 to -100 V, metal target power is 2.0 to 3.0 kW, sputtering gas pressure is 0.3 to 0.5 Pa, and deposition time is 2 to 5 min.

[0023] Preferably, the conditions for depositing the copper thin film are: Ar flow rate is 150-250 sccm, substrate bias voltage is -50 V, copper target power is 2.0 kW, and sputtering gas pressure is 0.4 Pa.

[0024] Preferably, the intermittent Ar + The bombardment conditions are as follows: Ar flow rate is 30 to 60 sccm, substrate bias voltage is -120 to -200 V, sputtering pressure is 0.05 to 0.2 Pa, ion bombardment is performed every 5 to 10 minutes, and the duration of each ion bombardment is 3 to 5 minutes.

[0025] The invention provides a method for preparing a flexible copper-clad laminate, comprising the following steps: using a high-energy non-metallic ion beam to etch and activate the surface of a polymer film to obtain an activated polymer film; using magnetron sputtering to inject metal ions onto the surface of the activated polymer film to obtain a polymer-metal interpenetrating network structure interface; depositing a copper film on the polymer-metal interpenetrating network structure interface, and while depositing the copper film, using intermittent Ar + The copper film is bombarded to obtain the flexible copper-clad laminate. The present invention effectively activates the surface of the polymer film by bombarding the polymer film with high-energy non-metallic ions, so that it can form a more effective bond with metal atoms, thereby improving the bonding strength of the copper film to the polymer surface. On the basis of high-energy non-metallic ion activation, a metal ion injection process is introduced to form a polymer-metal interpenetrating network structure interface, which can further significantly enhance the bonding strength of the copper film to the polymer film; at the same time, the present invention adopts intermittent high-energy, low-density Ar in the process of depositing the copper film. + The ion bombardment treatment process can effectively alleviate the internal stress of the surface copper film and reduce the risk of brittle peeling of the copper film under stress, while effectively overcoming the curling phenomenon of the polymer film due to the high internal stress of the copper film. The present invention can obtain a flexible copper clad laminate with high bonding strength and low internal stress through coordinated interface design and internal stress regulation. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The actual pictures of the hundred-grid test of the polyimide film without etching activation and the copper film in the flexible copper-clad laminate obtained in Comparative Examples 1 and 2;

[0027] Figure 2 The figure is a bar graph of the residual area of ​​the copper film in the flexible copper-clad laminate obtained by the polyimide film without etching activation and comparative examples 1 and 2 after the hundred-grid test;

[0028] Figure 3 XRD diagram of the polyimide film activated by etching and the copper film in the flexible copper clad laminate obtained in Comparative Example 1;

[0029] Figure 4 The figure is a hundred-grid test result diagram of the polyimide film that has not been etched and activated and the copper film in the flexible copper-clad laminate prepared in Example 1. DETAILED DESCRIPTION

[0030] The present invention provides a method for preparing a flexible copper clad laminate, comprising the following steps:

[0031] A high-energy non-metallic ion beam is used to etch and activate the surface of the polymer film to obtain an activated polymer film;

[0032] Using magnetron sputtering, metal ions are injected into the surface of the activated polymer film to obtain a polymer-metal interpenetrating network structure interface;

[0033] A copper film is deposited on the interface of the polymer-metal interpenetrating network structure, and while depositing the copper film, an intermittent Ar + The copper film is bombarded to obtain the flexible copper clad laminate.

[0034] In the present invention, unless otherwise specified, all preparation raw materials are commercially available products well known to those skilled in the art.

[0035] The invention adopts a high-energy non-metallic ion beam to etch and activate the surface of the polymer film to obtain the activated polymer film.

[0036] In the present invention, the polymer film is preferably a polyimide film or a polyethylene terephthalate film. The present invention does not have any special limitation on the thickness of the polymer film, and any thickness known to those skilled in the art can be used.

[0037] Before the etching activation, the present invention also preferably includes solvent cleaning of the polymer film; the solvent used for the solvent cleaning is preferably petroleum ether or alcohol; the solvent cleaning is preferably carried out under ultrasonic conditions, and the ultrasonic time is preferably 5 to 15 minutes, more preferably 8 to 12 minutes, and most preferably 9 to 11 minutes. The present invention does not have any special limitation on the frequency of the ultrasound, and the frequency well known to those skilled in the art can be used.

[0038] After the solvent cleaning is completed, the present invention preferably further includes blowing with nitrogen, placing the polymer film in a vacuum chamber and parallel to the surface of the sputtering target, and evacuating the chamber to a vacuum degree of preferably <1×10 -4 Pa, more preferably <5×10 -5 Pa.

[0039] In the present invention, the high energy non-metal ion beam is preferably Ar + ,Ar + +H + or Ar + +N + In the present invention, the Ar + The plasma is preferably generated by Ar, and the flow rate of the Ar is preferably 80 sccm; the Ar + +H + The plasma is preferably generated by Ar+H2, and the flow rates of Ar and H2 are preferably 80sccm and 20sccm respectively; + +N + The plasma is preferably generated by Ar+N2, and the flow rates of Ar and N2 are preferably 80 sccm and 20 sccm, respectively. In the present invention, the purity of Ar, H2 and N2 is preferably 99.99%.

[0040] In the present invention, the etching activation bias voltage is preferably -200 to -250 V, more preferably -210 to -230 V; the time is preferably 5 to 20 min, more preferably 10 to 15 min. The etching activation deposition voltage is preferably 0.08 to 0.3 Pa, more preferably 0.1-0.3 Pa, and most preferably 0.2 Pa.

[0041] After obtaining the activated polymer film, the present invention adopts magnetron sputtering to inject metal ions on the surface of the activated polymer film to obtain a polymer-metal interpenetrating network structure interface.

[0042] In the present invention, the metal element corresponding to the metal ion is preferably Cr, Ni, Nb or Cu. In the present invention, the metal ion is preferably prepared by magnetron sputtering a metal target. In the present invention, the metal target is preferably a Cr target, a Ni target, a Nb target or a Cu target; the purity of the Cr target, the Ni target, the Nb target or the Cu target is preferably 99.99%.

[0043] In the present invention, the conditions of the magnetron sputtering are preferably: the Ar flow rate is preferably 180 to 250 sccm, more preferably 190 to 240 sccm, and most preferably 200 to 220 sccm; the substrate bias voltage is preferably -60 to -100 V, more preferably -70 to -90 V, and most preferably -75 to -85 V; the metal target power is preferably 2.0 to 3.0 kW, more preferably 2.2 to 2.8 kW, and most preferably 2.4 to 2.6 kW; the sputtering gas pressure is preferably 0.3 to 0.5 Pa, more preferably 0.4 Pa; the deposition time is preferably 2 to 5 min, more preferably 3 to 4 min.

[0044] After obtaining the polymer-metal interpenetrating network structure interface, the present invention deposits a copper film on the polymer-metal interpenetrating network structure interface, and while depositing the copper film, intermittent Ar + The copper film is bombarded to obtain the flexible copper clad laminate.

[0045] In the present invention, the conditions for depositing the copper thin film are preferably that the Ar flow rate is preferably 150-250 sccm, the substrate bias voltage is preferably -50 V, the copper target power is preferably 2.0 kW, and the sputtering pressure is preferably 0.4 Pa.

[0046] In the present invention, the intermittent Ar + The bombardment conditions are preferably: the Ar flow rate is preferably 30 to 60 sccm, more preferably 40 to 50 sccm; the substrate bias voltage is preferably -120 to -200 V, more preferably -140 to -160 V; the sputtering gas pressure is preferably 0.05 to 0.2 Pa, more preferably 0.1 to 0.13 Pa; ion bombardment is performed every 5 to 10 minutes, and the time of each ion bombardment is preferably 3 to 5 minutes, more preferably 4 minutes.

[0047] The preparation method of the flexible copper clad laminate provided by the present invention is described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0048] Example 1

[0049] A polyimide film with a thickness of 100 μm was ultrasonically cleaned with petroleum ether for 15 min, dried with nitrogen, and placed in a vacuum chamber parallel to the surface of the sputtering target. The vacuum was evacuated until the vacuum degree of the chamber was less than 5×10 -5 Pa;

[0050] Ar gas was introduced into the vacuum chamber with an Ar flow rate of 80 sccm and a deposition pressure of 0.2 Pa. A bias voltage of -200 V was applied to the surface of the polyimide film to form an Ar + Plasma bombardment of the polyimide film surface for 10 min resulted in an activated polymer film;

[0051] Using magnetron sputtering, metal ions are injected into the surface of the activated polymer film. During the injection of the metal ions, the Ar flow rate is 200 sccm, the bias voltage applied to the polyimide film is -100 V, the Cr target sputtering power is 3.0 kW, and the deposition is 3 minutes; a polymer-metal interpenetrating network structure interface is obtained;

[0052] A copper film is deposited at the interface of the polymer-metal interpenetrating network structure. During the deposition of the copper film, the Ar flow rate is 200 sccm, the deposition gas pressure is 0.4 Pa, the substrate bias is -50 V, and the copper target power is 2 kW. After depositing the copper film for 10 minutes, the deposition of the copper film is stopped, the Ar flow rate is reduced to 50 sccm, the substrate bias is increased to -150 V, and the copper film is bombarded with Ar plasma for 5 minutes. This process is repeated alternately until the copper film thickness reaches 2 μm to obtain a flexible copper clad laminate.

[0053] Example 2

[0054] Referring to Example 1, the vacuum in the chamber is evacuated to a vacuum degree of less than 5×10 -5 After 30 s, Ar gas and N2 gas were introduced into the vacuum chamber, with an Ar flow rate of 80 sccm, an N2 flow rate of 20 sccm, and a deposition pressure of 0.2 Pa. A bias voltage of -200 V was applied to the surface of the polyimide film to form an Ar + +N + The surface of the polyimide film was bombarded with plasma for 10 minutes to obtain an activated polymer film. Then, a copper film was deposited on the surface of the activated polymer film using the same process parameters as in Example 1.

[0055] Example 3

[0056] Referring to Example 1, the vacuum in the chamber is evacuated to a vacuum degree of less than 5×10 -5 After 30 s, Ar gas and H2 gas were introduced into the vacuum chamber. The Ar flow rate was 80 sccm, the H2 flow rate was 20 sccm, and the deposition pressure was 0.2 Pa. A bias voltage of -200 V was applied to the surface of the polyimide film to form Ar + +H+ The surface of the polyimide film was bombarded with plasma for 10 minutes to obtain an activated polymer film. Then, a copper film was deposited on the surface of the activated polymer film using the same process parameters as in Example 1.

[0057] Comparative Example 1

[0058] A polyimide film with a thickness of 100 μm was ultrasonically cleaned with petroleum ether for 15 min, dried with nitrogen, and placed in a vacuum chamber parallel to the surface of the sputtering target. The vacuum was evacuated until the vacuum degree of the chamber was less than 5×10 -5 Pa;

[0059] A mixed gas of Ar and N2 was introduced into the vacuum chamber, with an Ar flow rate of 80 sccm, an N2 flow rate of 20 sccm, and a deposition pressure of 0.2 Pa. A bias voltage of -250 V was applied to the surface of the polyimide film to form an Ar + +N + Plasma bombardment of the polyimide film surface for 10 min resulted in an activated polymer film;

[0060] A copper film is deposited at the interface of the polymer-metal interpenetrating network structure. During the deposition of the copper film, the Ar flow rate is 200 sccm, the deposition gas pressure is 0.4 Pa, the substrate bias is -50 V, and the copper target power is 2 kW. After depositing the copper film for 10 minutes, the deposition of the copper film is stopped, the Ar flow rate is reduced to 50 sccm, the substrate bias is increased to -150 V, and the copper film is bombarded with Ar plasma for 5 minutes. This process is repeated alternately until the copper film thickness reaches 2 μm to obtain a flexible copper clad laminate.

[0061] Comparative Example 2

[0062] Referring to Comparative Example 1, the difference is that when preparing the activated polymer film, Ar gas is introduced into the vacuum chamber, the Ar flow rate is 80 sccm, the deposition pressure is 0.2 Pa, and a bias voltage of -200 V is applied to the surface of the polyimide film to form Ar + The surface of the polyimide film was bombarded with plasma for 10 minutes to obtain a flexible copper clad laminate.

[0063] Figure 1 The actual pictures of the 100-grid test of the copper film in the flexible copper-clad laminate obtained by the polyimide film without etching activation and comparative examples 1 and 2 are shown in FIG. Figure 1 It can be seen that Ar + +N + Ion etching significantly improved the bonding strength between the polyimide film and the copper film. Compared with the unetched sample, the bonding strength increased by 228% (e.g. Figure 2 As shown, Figure 2The residual area of ​​the copper film in the flexible copper-clad laminate obtained by the polyimide film without etching activation and comparative examples 1 and 2 is a bar graph. Meanwhile, the sputtering deposited copper film of the present invention has a (111) crystal plane preferred orientation (such as Figure 3 As shown, Figure 3 The XRD pattern of the copper film in the flexible copper-clad laminate obtained in Example 1 for etching activated polyimide film has excellent conductivity;

[0064] Figure 4 The results of the hundred-grid test of the polyimide film without etching activation and the copper film in the flexible copper-clad laminate prepared in Example 1 are shown in FIG. Figure 4 It can be seen that Ar + Etching activation combined with Cr ion implantation also greatly enhanced the bonding strength between the copper film and the polyimide film.

[0065] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a flexible copper clad laminate, characterized in that: The following steps are involved: A high-energy non-metallic ion beam is used to etch and activate the surface of the polymer film to obtain an activated polymer film; Using magnetron sputtering, metal ions are injected into the surface of the activated polymer film to obtain a polymer-metal interpenetrating network structure interface; A copper film is deposited on the interface of the polymer-metal interpenetrating network structure, and while depositing the copper film, an intermittent Ar + bombarding the copper film to obtain the flexible copper-clad laminate; The high energy non-metal ion beam is Ar + +N + ; The Ar + +N + Plasma generated by Ar+N2, wherein the flow rates of Ar and N2 are 80 sccm and 20 sccm respectively; The etching activation bias voltage is -200 to -250 V, and the time is 5 to 20 minutes; The intermittent Ar + The bombardment conditions are as follows: Ar flow rate is 30 to 60 sccm, substrate bias voltage is -120 to -200 V, sputtering pressure is 0.05 to 0.2 Pa, ion bombardment is performed every 5 to 10 minutes, and the duration of each ion bombardment is 3 to 5 minutes.

2. The preparation method according to claim 1, characterized in that The polymer film is a polyimide film or a polyethylene terephthalate film.

3. The preparation method according to claim 1 or 2, characterized in that: Before performing the etching activation, the polymer film is also cleaned with a solvent; The solvent used in the solvent cleaning is petroleum ether or alcohol; The solvent cleaning is carried out under ultrasonic conditions, and the ultrasonic time is 5 to 15 minutes.

4. The preparation method according to claim 1, characterized in that: The etching activation is carried out under vacuum conditions; The vacuum degree of the vacuum is <1×10 -4 Pa.

5. The preparation method according to claim 1, characterized in that: The metal element corresponding to the metal ion is Cr, Ni, Nb or Cu.

6. The preparation method according to claim 1 or 5, characterized in that: The conditions of the magnetron sputtering are: Ar flow rate is 180-250sccm, substrate bias voltage is -60--100V, metal target power is 2.0-3.0kW, sputtering gas pressure is 0.3-0.5Pa, and deposition time is 2-5min.

7. The preparation method according to claim 1, characterized in that: The copper film deposited strip The parameters are: Ar flow rate is 150-250sccm, substrate bias voltage is -50V, copper target power is 2.0kW, The sputtering gas pressure is 0.4Pa.

Citation Information

Patent Citations

  • Copper-clad plate and high-speed vacuum preparation method thereof

    CN111962034A

  • Vacuum sputtering continuous deposition copper film plating method

    CN113278934A